The Degree of Availability of Critical Thinking Skills among Arabic Language Teachers in Directorates Education in Karak Governorate, Jordan, from their Point of View - Tarawneh, Sudgeh Awad Falaah (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at identify the degree of availability of critical thinking skills among Arabic language teachers in the education directorates in Karak Governorate, Jordan, from their point of view, and to reveal the differences in that according to the variables of gender, academic qualification and the number of years of experience. and the researcher prepared a questionnaire consisting of (48) items distributed on (7) skills, namely: (analysis, induction, interpretation, conclusion), Calendar), and the indications for their validity and reliability were verified. Where a stratified random sample of (193) teachers was chosen from among the teachers of the Arabic language in the directorates of education in the governorate of Karak, The study found that the degree of availability of critical thinking skills among Arabic language teachers from their point of view was medium, with an arithmetic mean (3.42) and The skill of "deduction" came first, with an arithmetic average of (3.73), And with a high degree, while the “evaluation” skill came in the last place, with an arithmetic average of (2.93), and a medium degree. It also indicated that there are no statistically significant differences at the level of significance (α≤0.05) in the degree of availability of thinking skills. The critic among Arabic language teachers is attributed to gender, while it was found that there are statistically significant differences attributable to academic qualification and in favor of higher qualification (postgraduate studies), and the existence of statistically significant differences due to years of experience and in favor of those with higher experience.